Increased Anxiety and Length of Treatment Associated With Depressed Patients Who are Readmitted to Collaborative Care - Kurt B. Angstman MS, MD (Journal of Primary Care & Community Health, 2011)
In 2008, the Institute for Clinical Systems Improvement (ICSI) in Minnesota implemented a model of collaborative care management (CCM) for treatment of depression in primary care. This resulted in significant improvements on both clinical response and remission over usual care, although an increase in utilization metrics has been observed. Mental health comorbidities have previously been significantly associated with an increased likelihood of not responding to initial treatment. This retrospective study hypothesized that patients with mental health comorbidities are more likely to be associated with patients who were readmitted into CCM with recurrent depression. A total of 145 patients who had completed CCM were studied; of these, 32 were diagnosed with recurrent depression and were readmitted to CCM, and 113 were in remission for at least 4 months. There were no statistically significant demographic differences between the 2 groups. The initial screening GAD-7 score for anxiety was significantly increased in the readmission group (12.81 vs 9.20, P = .001) as was the average length of treatment from initial diagnosis to remission (168.09 vs 120.99 days, P = .002). All other initial screening tests were not different between the groups. When controlling for the independent variables by multiple logistic regression, the odds ratio for GAD-7 was 1.1156 (CI = 1.0.192 to 1.2212, P = .0177) and for days of treatment in CCM was 1.0123 (CI = 1.0041 to 1.0206, P = .0033). Patients who are readmitted to CCM for recurrent depression have a statistically increased risk of associated anxiety and a longer treatment course than those who have remained in remission for at least 4 months.